Research trends in the use of artificial intelligence in higher education - Akhmadieva, Roza Sh.; Kalmazova, Nadezhda A.; Belova, Tatyana; Prokopyev, Alexey; Molodozhnikova, Natalia M.; Spichak, Valentina Yu (Frontiers in Education, 2024)
The latest technological advancements have greatly interested researchers in artificial intelligence (AI) in education. In parallel, researchers have expressed concern about using and applying AI in education. However, there is a shortage of research that comprehensively and holistically examines trends in the use of AI in higher education. Hence, this study aimed to comprehensively analyze and assess AI research trends in higher education. In the SCOPUS database, we conducted a bibliometric analysis of 1563 articles on research on AI in education. Our results revealed that the use of AI in education has increased dramatically from 2004 to 2023. In particular, a dramatic increase and peak exist after 2019. We also found limited interaction among scholars studying AI. Furthermore, our findings indicate that most of the most influential institutions are located in developed countries. Moreover, our findings demonstrated that AI research primarily concentrated on comprehending the impact of AI-based instruction, with the majority of these studies taking place in engineering education between 2017 and 2020. We also noticed that research on medical education in higher education occurred between 2015 and 2017. In addition, before 2015, research used AI in medical education as a teaching method to implement problem-based learning in higher education.In recent years, researchers have studied the use of AI in education. Upon this line of research, scholars have conducted review studies to examine the status of using AI in higher education research. However, the existing literature reviews have mainly focused on systematic reviews of AI in the higher education context (Bond, et al.